2007
DOI: 10.1055/s-2007-962943
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Katarakt assoziiert mit Mikrokornea und Glukosurie: Ein neues Syndrom

Abstract: We have defined a new syndrome, consisting of the association of juvenile cataract, microcornea and renal glucosuria. The pattern of inheritance is autosomal-dominant. Genotyping is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…4,5 Of particular interest to this work is a Swiss family with juvenile cataract, associated with microcornea and renal glucosuria. 7 Although renal glucosuria is not considered a disease, affected individuals show characteristic elevation of glucose concentration in the urine, without evidence of other renal tubular defects. The pattern of inheritance has been described as codominant with variable penetrance.…”
mentioning
confidence: 99%
“…4,5 Of particular interest to this work is a Swiss family with juvenile cataract, associated with microcornea and renal glucosuria. 7 Although renal glucosuria is not considered a disease, affected individuals show characteristic elevation of glucose concentration in the urine, without evidence of other renal tubular defects. The pattern of inheritance has been described as codominant with variable penetrance.…”
mentioning
confidence: 99%
“…These pseudogenes are particularly expressed in the testis (Von Figura et al 2001) and brain (Bayou et al 2008). Recently, a second protein (MCT12) identified several years ago (Halestrap and Meredith 2004) has been associated to patients with a particular syndrome (Vandekerckhove et al 2007;KloeckenerGruissem et al 2008) and Cr transport defect (Abplanalp et al 2013). This protein is encoded by SLC16A12 gene that is located on 10q23.31 chromosome (Halestrap and Meredith 2004;Kloeckener-Gruissem et al 2008;Abplanalp et al 2013).…”
Section: Metabolism Of Creatinementioning
confidence: 96%
“…Concerning CJMG associated with MCT12 defect, urine Cr has not been evaluated in patients with this disorder (Vandekerckhove et al 2007;KloeckenerGruissem et al 2008). However, urine Cr concentration in SLC16A12 KO rats was high (Abplanalp et al 2013).…”
Section: Potential Applications To Prognosis Other Diseases or Condmentioning
confidence: 97%
“…A heterozygous mutation (c.265G>A; p.(A89T)) added glycosuria to the phenotype of an otherwise unrelated disease, juvenile cataract with microcornea, caused by monoallelic SLC16A12 mutations. Because SLC16A12 was found to be also expressed in the kidney, the association had been initially reported as a new syndrome [102,103]. Further segregation studies demonstrated that glucosuria was a separate phenotype [104].…”
Section: Mutations Outside the Known Pattern For The Conditionmentioning
confidence: 98%